Windows 10 for dummies - Rathbone, Andy (Hoboken, New Jersey John Wiley & Sons, 2015)
Overview: The fast and easy way to get up and running with Windows 10. Windows 10 For Dummies covers the latest version of Windows and gets you up and running with the changes and new features you'll find in this updated operating system. Packed with time-saving tips to help you get the most out of the software, this helpful Windows 10 guide shows you how to manage Windows tasks like navigating the interface with a mouse or touchscreen, connecting to the web, and troubleshooting problems and making quick fixes. Assuming no prior knowledge of the software, Windows 10 For Dummies addresses the updates to Windows and shows you how to get things accomplished. Focusing on the features you'll go to again and again, this new edition of this bestselling tech book will have you quickly finding files, connecting to the Web, gathering your email and social accounts in one spot, managing apps, creating and managing accounts, using online tools, customizing your settings, and so much more - making you a Windows whiz in no time. Helps you navigate the twists and turns of the updated Windows interface. -- Provides easy-to-follow answers to all of your Windows questions. -- Illustrates the new features of Windows 10. -- Quickly gets you up to speed on figuring out the changes to the latest version of Windows. -- Whether you're new to Windows or just looking to get up to speed on what's changed in its latest release, this is the only resource you'll need
Introduction: -- Part I: Windows 10 Stuff Everybody Thinks Your Already Know -- Part II: Working with Programs, Apps, and Files -- Part III: Getting Things Done on the Internet -- Part IV: Customizing And Upgrading Windows 10 -- Part V: Music, Photos, and Movies -- Part VI: Help! -- Part VII: The Part of Tens -- Index
Includes index
13
Keywords: Microsoft Windows (Computer file); Microsoft Windows (Computer file); Operating systems (Computers); Operating systems (Computers)